Mitochondria: Master Regulator of Metabolism, Homeostasis, Stress, Aging and Epigenetics - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Mitochondria became a driving force in evolution due to their ability to manufacture adenosine triphosphate (ATP) through respiration. The functioning of mitochondria within eukaryotic cells has evolved dramatically as a result of evolution. Recent research has revealed mitochondria form plasticity to keep the cell's needs and function.CONTENT: Mitochondria have long been regarded as the cell's "powerhouse," providing energy for cell metabolism through oxidative phosphorylation (OXPHOS). A lot of physiological processes were known to be mediated by mitochondria including immunity and autophagy, cell death mechanism, and stem cell reprogramming. Mitochondria can change their shape to form a tubular network that is controlled by fission and fusion processes. Mitochondrial dynamics is the equilibrium between these two opposing processes that regulates mitochondrial number, size, and positioning within the cytoplasm.SUMMARY: All of these discoveries opened up new research avenues and revealed new targets for targeted medication development. Calorie restriction, and the mimetic agents were developed to increase mitochondria biogenesis to improve human lifespan.KEYWORDS: mitochondria, metabolism, homeostasis, stress response, aging, epigenetic